Development of the short Creative Expression Interest Scale based on item response theory - Zhao, Peng Juan; Gao, Xu Liang; Zhao, Nan; Luo, Zhao Sheng (Frontiers in Psychology, 2022)
This study develops a Short Creative Expression Interest Scale among Chinese freshmen, based on the perspective of Item Response Theory (IRT), and explores the mechanism among Creative Expression Interest, openness personality and self-efficiency. 959 valid Chinese freshmen took part in the Creative Expression Interest survey. Researchers apply unidimensionality, test fit, item fit, discrimination parameter, differential item functioning of the initial data and obtain a short Creative Expression Interest scale. Subsequently, researchers construct a moderated mediation model between openness personality and Creative Expression Interest. Results show that: the Short Creative Expression Interest scale meets the IRT psychometric measurement requirements; Pearson’s correlation of the theta between the short and full-length creative expression interest scale is 0.92; Besides, there is a significant correlation among openness personality, General Self-efficacy and Creative Expression Interest with each other; the relationship between openness personality and Creative Expression Interest is mediated by General Self-efficacy; gender plays a moderating role between openness personality and general self-efficacy. These suggest that the short Creative Expression Interest scale among Chinese freshmen is a reliable and valid instrument and there is a moderated mediation model between openness personality and Creative Expression Interest.